HUBUNGAN MAKANAN DAN MINUMAN YANG BERSIFAT IRITAN DENGAN KEJADIAN GASTRITIS DI DESA PENYESAWAN WILAYAH KERJA PUSKESMAS KAMPAR - Ade Dita Puteri (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2021)
Food and drinks that are irritants are very influential on the incidence of gastritis. Gastritis is the most common disorder encountered in the clinic because it is diagnosed based solely on clinical symptoms. This situation can result from food and drink irritating the gastric mucosa, excessive gastric mucosa secretions by the stomach's own secretions and sometimes due to bacterial inflammation. The purpose of this study was to determine the relationship between food and drink irritants with the incidence of gastritis in the village of Penyesawan, the working area of the Kampar Health Center in 2021. The design of this study used an analytical research design with a cross-sectional design. The sample in this study were the families of 229 people in the village of Penyesawan in the working area of the Kampar Health Center. The sampling technique was simple random sampling. The research instrument used a questionnaire and data processing was carried out univariate and bivariate. Research results Based on statistical tests, it was found that X2 = 10.861 with P value = 0.002 (p